ANALISIS DETERMINAN PEMANFAATAN LAYANAN ANTENATAL DI SUMATERA SELATAN - Rini Mutahar (Publikasi Penelitian Terapan dan Kebijakan, 2020)
Maternal death can generally be prevented if complications of pregnancy and other high-risk situation can be detected early. How early detection can be performed at antenatal care services by increasing coverage of antenatal care both K1 and K4. This study aims to determine the factors that influence the utilization of antenatal care (ANC) in South Sumatra. This study represents further analysis of the Indonesia Demographic Health Survey (IDHS) 2007 which uses cross sectional design. Analysis of data using multiple logistic regression. From the results, frequency of ANC quite as much as 58%, the completeness of the ANC of> 2 types of service, as much as 41.2% and most mothers do worse antenatal care (61.2%) 3. Women who experienced pregnancy complications are at risk from using the services of antenatal 2.59 times greater than in women who did not experience pregnancy complications after being controlled by variable residence, accompanied by husband antenatal care and age (95% CI 1:27 to 5:32). Mothers who are not accompanied her husband during the visit of the ANC has the advantage of risk antenatal care is almost 2 times greater than in women who accompanied her husband during the visit of the ANC. It is recommended to further improve the monitoring of village midwives towards antenatal care, not only in frequency but also on the completeness ANC ANC examination and improve counseling for pregnant women on antenatal care